2010
DOI: 10.1002/jcp.22267
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II regulates differentiation of ameloblasts via intracellular pH‐dependent JNK signaling pathway

Abstract: Differentiation of ameloblasts from undifferentiated epithelial cells is controlled by diverse growth factors, as well as interactions between epithelium and mesenchyme. However, there is a considerable lack of knowledge regarding the precise mechanisms that control ameloblast differentiation and enamel biomineralization. We found that the expression level of carbonic anhydrase II (CAII) is strongly up-regulated in parallel with differentiation of enamel epithelium tissues, while the enzyme activity of CA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
(51 reference statements)
0
21
1
Order By: Relevance
“…Acid-base balance in the extracellular matrix and intracellular lumens is maintained by a complex regulatory network involving multiple ion transporters and carbonic anhydrases (Dogterom and Bronckers, 1983; Lin et al, 1994; Wright et al, 1996a,b; Arquitt et al, 2002; Lyaruu et al, 2008; Paine et al, 2008; Bronckers et al, 2009, 2010; Josephsen et al, 2010; Wang et al, 2010; Lacruz et al, 2010a,b, 2012c, 2013a; Chang et al, 2011; Duan et al, 2011; Duan, 2014; Jalali et al, 2014; Reibring et al, 2014; Wen et al, 2014). Although details regarding the mechanism of pH control are yet to be clarified, the critical roles of many genes in maturation-stage pH regulation have been implicated by previous studies on transgenic animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acid-base balance in the extracellular matrix and intracellular lumens is maintained by a complex regulatory network involving multiple ion transporters and carbonic anhydrases (Dogterom and Bronckers, 1983; Lin et al, 1994; Wright et al, 1996a,b; Arquitt et al, 2002; Lyaruu et al, 2008; Paine et al, 2008; Bronckers et al, 2009, 2010; Josephsen et al, 2010; Wang et al, 2010; Lacruz et al, 2010a,b, 2012c, 2013a; Chang et al, 2011; Duan et al, 2011; Duan, 2014; Jalali et al, 2014; Reibring et al, 2014; Wen et al, 2014). Although details regarding the mechanism of pH control are yet to be clarified, the critical roles of many genes in maturation-stage pH regulation have been implicated by previous studies on transgenic animal models.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA used for real-time PCR analysis was prepared using the miScript II RT Kit with miScript HiFlex Buffer (Qiagen). To detect the expression changes in the genes that have been identified to be involved in maturation-stage pH regulation (Dogterom and Bronckers, 1983; Wright et al, 1996a,b; Andrejewski et al, 1999; Arquitt et al, 2002; Lyaruu et al, 2008; Paine et al, 2008; Bertrand et al, 2009; Bronckers et al, 2009, 2010, 2011; Josephsen et al, 2010; Wang et al, 2010; Lacruz et al, 2010a,b, 2011, 2012b,c, 2013b; Chang et al, 2011; Duan, 2014; Jalali et al, 2014; Yin et al, 2014, 2015), real-time PCR reactions were performed on a CFX96 TouchTM Real-Time PCR Detection System (Bio-rad Life Sciences) with iQ SYBR® Green supermix (Bio-rad Life Science) and mouse-specific primers (Table 1). The Ct values were normalized to those of Actb ( Beta-actin ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During maturation-stage tooth development, ameloblasts have been identified to be involved in a series of highly orchestrated events including matrix turnover, ion transport, pH regulation, calcium handling and cell apoptosis210. Previous studies have focused on the signaling pathways of enamel maturation primarily at genetic level2930313233; however the involvement of epigenetic regulatory mechanisms in this process has not been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that CA II, an isozyme of CA IX distributed in cytosol, regulates the differentiation of ameloblasts by modulating cytosolic pH [15]. Although immunohistochemical analysis revealed that CA IX is distributed in chondrocytes in human embryos [16], to the best of our knowledge, there is no report of the function of CA IX in chondrocytes.…”
Section: Introductionmentioning
confidence: 96%